2017
DOI: 10.1371/journal.pone.0179134
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurogenesis and volume in migrating and wintering semipalmated sandpipers (Calidris pusilla)

Abstract: Long distance migratory birds find their way by sensing and integrating information from a large number of cues in their environment. These cues are essential to navigate over thousands of kilometers and reach the same breeding, stopover, and wintering sites every year. The semipalmated sandpiper (Calidris pusilla) is a long-distance migrant that breeds in the arctic tundra of Canada and Alaska and winters on the northeast coast of South America. Its fall migration includes a 5,300-kilometer nonstop flight ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 83 publications
(83 reference statements)
2
15
0
Order By: Relevance
“…It is important to note that in previous work we detected an increase in volume in wintering C. pusilla when compared to migrating ( de Morais Magalhães et al, 2017 ). In the present results this reduction in volume of hippocampal formation was not detected, suggesting that other cells of the hippocampal formation and associated neuropil may have effect over the volume and more data is necessary to clarify what generates the observed volume fluctuation.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…It is important to note that in previous work we detected an increase in volume in wintering C. pusilla when compared to migrating ( de Morais Magalhães et al, 2017 ). In the present results this reduction in volume of hippocampal formation was not detected, suggesting that other cells of the hippocampal formation and associated neuropil may have effect over the volume and more data is necessary to clarify what generates the observed volume fluctuation.…”
Section: Discussionmentioning
confidence: 51%
“…Because we have no information in the literature about potential influence of sex and age on hippocampal astrocytes morphology in long-distance migratory birds, and we did not measure the age of individuals in our sample due to technical limitations, it is difficult to discuss these potential influences in detail. However, experience and sex are important variables that have been previously demonstrated to influence hippocampal-dependent tasks in birds ( Astié et al, 2015 ; Rensel et al, 2015 ; Guigueno et al, 2016 ; Bingman and MacDougall-Shackleton, 2017 ), and migratory behavior is accompanied by hippocampal morphological changes including volume and neurogenesis ( Barkan et al, 2016 , 2017 ; de Morais Magalhães et al, 2017 ). Thus, these variables should be considered in future studies of hippocampal astrocytes morphologies in long-distance migratory birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of neurons in the adult bird brain was demonstrated in the ventricular hyperestriatum using [H 3 ]-thymidine [4]. Since then, several studies have revealed the existence of adult neurogenesis as a well-established and widespread phenomenon in birds [82,83,84,85,86].…”
Section: Adult Neurogenesis In Birdsmentioning
confidence: 99%
“…The generation and survival of new neurons is influenced by several life-related factors, such as food restriction [94], seasonality [95], migratory experiences [86], migratory distance [96], and learning and memory [97,98].…”
Section: Adult Neurogenesis In Birdsmentioning
confidence: 99%